Statistical Analysis of Factors Affecting Grade Point Average of Level 100 Students: A Case Study of University of Ghana Legon Campus - Anani Lotsi (USN Kolaka, 2019)
Grade Point Averages (GPA) are known to give fair assessment of students performance in an academic degree programme, and students ability to successfully complete a degree programme is also known to depend on their level 100 GPA. In this paper we sought to determine factors that significantly affect academic performance of Level 100 students of the University of Ghana. Questionnaires method was used to collect the data for analysis, and regression analysis was carried out on the data to determine the effect of gender, residential status, and previous high school on Grade GPA of level 100 students. At the end of the analysis it was found that the above mentioned factors do not significantly affect GPA. However, we found that the programme a level 100 student offers, significantly affects the student’s GPA.